Assessing the contribution of recreational sea angling to the English economy. (September 2017) - Roberts, Annette; Munday, Max; Roche, Neil; Brown, Adam; Armstrong, Mike; Hargreaves, Jodie; Pilgrim-Morrison, Sarah; Williamson, Kevin; Hyder, Kieran
Abstract: Sea angling has been shown to be a high value activity with significant expenditure by individuals on their sport. Deriving estimates of the economic contribution of recreational sea angling is important in a number of related policy contexts, from tourism management and economic development policy, to the sustainable management of inshore fish stocks. This paper reveals some of the challenges in understanding the economic effects associated with recreational sea angling, and provides estimates of the economic value of recreational sea angling in England. The results were derived from research undertaken in England in 2011-13, which was conducted as part a wide ranging government-funded study, Sea Angling 2012, that estimated sea angler catches, spending and activity. Recreational sea angling made a significant contribution to the economy, supporting just over £2 billion of total spending, and 23, 600 jobs in England in 2012-13. The implications of these results are discussed in the context of the management of recreational sea angling in England. Highlights: The paper estimates the economic contribution of recreational sea angling to England. Average angler spending, on trips and major items, was almost £1400 in 2012-13. Sea angling supported around £2 billion of spending and 23, 600 jobs in England.